Roberto Caracciolo da Lecce (1425-1495) - Mariani, Giacomo, author.
1 online resource.
Keywords: In the second half of the fifteenth century, Roberto Caracciolo’s preaching touched the most important cities of Italy, and met with wide and resounding success. His sermons were read and diffused throughout Italy and Europe, propelled by the emergence of the printing press industry. This book provides a new and comprehensive study of his life, preaching and writing, replacing outdated resources and adding new and hitherto unknown data. It offers a reference work on a relevant social, intellectual and religious actor of Renaissance Italy and a reading of those times through the life and works of a celebrated preacher.